Investasi Publik pada Sektor Pertanian di Era Otonomi (Forum Penelitian Agro Ekonomi, 2016)
EnglishThe paper aims to review the role of government and its policy instruments that enhance economic development and sectoral growth, especially those that relate to investments on infrastructural development such as irrigation and research and extension on agricultural commodities and sector. By appropriate identification of public investment needs and development of infrastructure that is required most by community and region, given its existing condition, agriculture can be pushed to develop forward. This in turn will move the economy further. Public investment on rural infrastructure, agricultural research, and public health and education are incentive factors that enable agriculture and non-agriculture to grow, by further generating employment opportunities, incomes and affordable food for the community. Research may have bias impacts on different group of the population The impact could be mitigated, however, if existing infrastructure services and rural institutions were bound to support research and development. IndonesianTujuan makalah ini adalah menelaah peranan pemerintah dan instrumen kebijakannya untuk mendorong pembangunan ekonomi dan perkembangan sektor-sektor ekonomi,terutama yang berkaitan dengan investasi pembangunan infrastruktur irigasi,penelitian dan penyuluhan yang diamati dalam komoditas dan sektor pertanian. Identifikasi kebutuhan investasi publik yang dilakukan dengan tepat dan pembangunan prasarana dan sarana yang sesuai dangan kebutuhan dan kemampuan masyarakat dan wilayah akan mendorong pembangunan pertanian. Dorongan ini pada gilirannya akan menggerakan perekonomian lebih cepat lagi. Investasi pemerintah dalam infrastruktur pedasaan,penelitian pertanian,kesehatan dan pendidikan masyarakat pedesaan mendorong pertumbuhan pertanian dan nonpertanian,yang menyebabkan semakin meningkatnya kesempatan kerja, pendapatan dan pangan yang lebih murah bagi penduduk. Penelitian mempunyai dampak yang berbeda bagi kelompok masyarakat yang berbeda. Namun,apabila jasa infrastruktur dan kelembagaan pedesaan yang tersedia berjalan seiring mendukung penelitian dan pengembangan,dampak diskriminatif tersebut dapat dikurangi
Keywords: public investment; infrastructure; agricultural sector; autonomy; investasi publik; infrastruktur; sektor pertanian; otonomi